The era of ever-larger dwellings in Germany is coming to an end - Konstantin Kholodilin; Sebastian Kohl (DIW Weekly Report, 2026)
Over the past 150 years, living space consumption has increased significantly-in Germany from less than half a room to almost two rooms per capita. The average living space per person more than doubled between 1956 and 2024, reaching 49.2 square meters. Rising incomes enabled the construction of ever larger dwellings which led to improved living conditions. Today, the majority of people live in spacious dwellings instead of cramped conditions. At the same time, this means that more resources per capita are required for construction, maintenance, and heating. However, the early 2000s marked a turning point: the size of newly built apartments began to decline. This decline has been particularly noticeable in rental apartments in big cities since the 2010s. This Weekly Report attributes the trend reversal, which can be observed not only in Germany but also in many other countries, to three factors: shrinking household sizes, rising real estate prices and rents, as well as new land use regulations that restrict the construction of single-family homes. The results suggest that the demand for housing is undergoing a structural change, with smaller, more energy-efficient, apartments becoming more important.
Keywords: C32; E27; E32; 330; average housing size; residential construction; consumption of floor space